Photo-Oxidation of PVC-Coated Membrane Material Under Different Light Sources - Yang, Xudong; Xu, Xiaowei; Yan, Yongsheng; Wang, Fangjuan (Asian Journal of Chemistry, 2014)
The effects of accelerated weathering tests on PVC-coated membrane material are studied to establish the possible correlation between different light sources and ultraviolet radiation intensities. Two light sources and three UV radiation intensities were provided in accelerated weathering tests, they are 1 UVB-313 lamp, 4 UVB-313 lamps and 4 UVA-340 lamps, respectively, to study the influences of different UV irradiation intensities and light sources on photo-oxidation of the PVC-coated membrane material. The tensile properties of the PVC-coated samples under different accelerated weathering conditions were then measured. In addition, FTIR (Fourier Transform Infrared) and UV-visible (ultraviolet visable range) were used to analyze the samples. The study shows that the photo-oxidation mechanism of PVC weathering samples does not change under the two different light sources and different UV radiation intensities. However, the study indicates that the weathering degree of PVC samples is incongruous when accepted equivalent radiation energy. The difference between the luminescence spectra of the two light sources is the main reason. Therefore, the Reciprocity law does not apply to predict the performance of PVC-coated membrane material used outdoors. However, according to the different luminescent spectrum of the two light sources, the effective UV radiation was introduced in the Schwarzschild’s law. Eventually, the correlation of different weathering results under different UV radiation intensities and light sources could be better established.